Clinical management of the vertical dimension with fixed prosthesis and removable partial denture, with rotational insertion axis - Pizarro, Elías (2018)
The alteration of the vertical dimension can be caused by different factors, among which, we find partial loss of dental pieces, pathological wear of the occlusal surfaces that are caused by different etiologies, being one of the most common bruxism. This results in alterations in the stomatognathic system that causes aesthetic and functional sequelae. That is why the importance of theoretical and clinical knowledge of partial edentulism when the vertical dimension is altered, because as we know there are currently many biomaterials and techniques to rehabilitate a patient with these characteristics, however, all part of a correct diagnosis. Traditionally different methods have been used to establish the appropriate vertical dimension; however, there is not yet a single method capable of providing total accuracy. The objective of this work is to share the approach to a patient with alteration of the vertical dimension through the manufacture of fixed prosthesis and PPR with double insertion axis. Main data a complete 82-yearold edentulous patient who had a decrease in the vertical dimension due to parafunctional habit (centric and eccentric bruxism) was completely rehabilitated. Main comments: The results were satisfactory for the patient since full rehabilitation was achieved through combined prosthesis (fixed and removable) thus restoring the vertical dimension and therefore having functional and aesthetic results. Conclusions: The use of fixed prosthesis and PPR double axis of insertion is an alternative of treatment that allows returning of optimal form the functions of the oral cavity giving like result the comfort of the patient.